A Study Of Kurnia Ngayuga Wibowo's Experimental Photography “Memory Lane‘’ - Abdul Aziz Al Hakim; Raden Bima Sakti Arnanda A; Khaerudin Imawan; Rizky Dwi Andini; Dedet Erawati (Journal Of Social Science (JoSS), 2024)
This study focuses on Kurnia Ngayuga Wibowo's experimental photography work Memory Lane, featured in several exhibitions, including the Permata Youth Photostory and the Bandung Photography Triennale. The artwork depicts the artist's imagination of Admiral Cheng Ho's arrival in Cirebon, using photography techniques and mixed media elements such as red thread and gold markers. This research aims to understand the artwork through art criticism using Edmund Burke Feldman's theory, which includes description, formal analysis, interpretation, and evaluation. This research employs a qualitative method with an in-depth analysis of the visual elements in the photographic work. The results indicate that Memory Lane is an example of experimental photography that combines various artistic elements to convey a historical narrative creatively. In conclusion, the work successfully provides a new perspective on experimental photography and highlights the importance of historical archiving through visual media.